Small scale testing of IN718 single crystals manufactured by EB-PBF - Gotterbarm, Martin; Seifi, Mohsen; Melzer, Daniel; Džugan, Jan; Salem, Ayman A.; Liu, Zhong H.; Körner, Carolin (Additive Manufacturing, 2020)
Due to the nature of the Electron Beam Powder Bed Fusion (EB-PBF) process, it offers an opportunity to produce parts with desired localized mechanical properties by influencing the microstructure evolution of built components through process parameters adjustment. This research demonstrated this potential, not only producing IN718 components with custom grain structures but also successfully produced IN718 single crystal components. At this moment, EB-PBF is widely associated with low volume manufacturing when compared to conventional manufacturing processes. For this reason, small scale testing (SST) is also utilized in this research as an efficient and practical approach to assess fracture behavior of EB-PBF manufactured components.
CRIS-Team Scopus Importer:2020-07-31
Keywords: EBSD; Electron beam; Powder Bed Fusion; Single crystal; Tensile test